PI-based finite time consensus control for dual active bridge DC-DC converter - Shi, Ruxin (2019)
The dissertation mainly focused on the control of dual active bridge (DAB) DC-DC converter. With the increasing concern of renewable energy sources issue, power electronic converters are widely applied in distributed generation systems. To achieve the bidirectional power flow in the renewable energy systems, dual active bridge (DAB) DC-DC converter is studied by researchers with high interest. This paper presents an advanced control method to improving the steady-state and dynamic performance of DAB by combining finite time control (FTC) with traditional PID controller. This method has been successfully applied in buck converter. However, it has not been applied to DAB. Therefore, the FTC based on DAB single phase shift control strategies will be discussed in the paper. The comparison of simulation results for traditional PID controller and the combination of PID controller and FTC were shown in the last part of the paper.